Rearrangement of the transmembrane domain interfaces associated with the activation of a GPCR hetero-oligomer - Li Xue (Nature Portfolio, 2019)
G protein-coupled receptors (GPCRs), such as GABAB, can integrate extracellular signals via allosteric interactions within dimers and oligomers. Here authors use crosslinking and identify two transmembrane interfaces in GABAB which undergo a concerted rearrangement upon agonist activation.